(3eUHGM eTcGI GdCfhGQ ef UMjM MOjK GdeNJGQs - (3CHh GdVjGA YHO GdQMef Hf Ydj dGTjHGfi GdRHjOi , GHf GdOjHYs; (3GdScGcj , SQGL GdOjf CHh jYbhH jhSa Hf CHj HcQ Hf eMeO Hf Ydj GdScGcj GdNhGQRej GdMfaj, GdScGcj,J (B626 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CHQR eUHGM eTcGI GdCfhGQ ef MOjK GdeUWai CeG HYO s
(3BNQgG (B:s
(3BNQg ef HGH (B" (3KhGH gPg GdCeI (B" (3bhdg (B: (3hai R hGfg bGd agh aVdi ChJjg ef CTGA , QhGI GdHNGQi , hgPG BNQ eG jSQ Gddg LeYg ef gPG GdcJGH s
(3GdfSNI HgG MhGTs
(3GdfSNI ebGHdI SfI (B1000(3g`s
(3Ydi ghGeTgG JbjjOGJs
(3cJHJ GdYfGhjf hHYV GdcdeGJ HGdMeQI s
(3HgG fXGe GdJYbjHI s
(3bQf GdfSN (B:s
Keywords: (3GdMOjK h GdeUWdMs